Intractable hiccups: the role of cerebral MR in cases without systemic cause. - Marsot-Dupuch, K; Bousson, V; Cabane, J; Tubiana, J M (American Journal of Neuroradiology, 1995)
PURPOSE To look for central nervous system abnormalities as possible causes of intractable hiccups. METHODS Of a series of 50 patients with chronic (ie, lasting more than 48 hours) hiccups, a prospective study identified a subgroup of 9 patients with no clinical or gastroesophageal abnormalities (according to endoscopy, pH monitoring and manometry). We performed in all 9 patients brain and upper cervical cord MR examination with precontrast and postcontrast T1- and T2-weighted sequences. A study of the last cranial nerves was done with thin T2-weighted imaging (constructive interference in a steady state sequence). The cervical cord and parapharyngeal space were systematically explored using coronal T2- and sagittal T1-weighted imaging. RESULTS Five of these 9 patients had definite MR abnormalities located in the temporal lobe (3 cases), cerebellopontine angle (1 case), or areas of high signal intensity compatible with demyelination (1 case). The relationship between hiccups and infratentorial abnormalities in 2 cases was doubtful (vascular loop and prominent posterior condylar canal). MR findings in 2 cases were considered normal. CONCLUSIONS Brain MR is a useful investigation in patients with chronic hiccups when gastroesophageal lesions are either excluded or too mild to account for an intractable hiccup.